2016
DOI: 10.1002/14651858.cd012004
|View full text |Cite
|
Sign up to set email alerts
|

Motor control exercise for chronic non-specific low-back pain

Abstract: There is very low to moderate quality evidence that MCE has a clinically important effect compared with a minimal intervention for chronic low back pain. There is very low to low quality evidence that MCE has a clinically important effect compared with exercise plus EPA. There is moderate to high quality evidence that MCE provides similar outcomes to manual therapies and low to moderate quality evidence that it provides similar outcomes to other forms of exercises. Given the evidence that MCE is not superior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
325
0
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(380 citation statements)
references
References 172 publications
5
325
0
24
Order By: Relevance
“…high energy laser, shock wave or electrostimulation) is not indicated. it is recommended supervised motor therapy, behavioral therapy, massage aimed at normalizing the resting tension of the muscles and improvement of their trophics [26][27][28][29][30][31][32][33][34].…”
Section: Treatmentmentioning
confidence: 99%
“…high energy laser, shock wave or electrostimulation) is not indicated. it is recommended supervised motor therapy, behavioral therapy, massage aimed at normalizing the resting tension of the muscles and improvement of their trophics [26][27][28][29][30][31][32][33][34].…”
Section: Treatmentmentioning
confidence: 99%
“…The PA&E in this trial were based and modified from previous studies [193,216] which reported improvements in pain intensity and strength for women with pain in the neck-and shoulder muscles. PA&E in various combinations are often used for the treatment of chronic pain [3,[33][34][35][36][37][38][39]. However, despite the large amount of research on PA&E as treatment for chronic pain, there is still a lack of knowledge on physiological effects mechanisms behind the positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in accordance with the suggestion that chronification of pain might be related to an imbalance between facilitating and inhibitory neurobiological systems [47,236], it is important to highlight the potential of PA&E to impact both ascending pain inducing activities as well as pain modulatory and descending activities in the nervous system. In future studies, the clinical effect on pain intensity and function as a result of different types of PA&E might not be of main interest to evaluate further, as several reviews [3,33,34,[36][37][38][39] and a metaanalyse [35] consistently shows that PA&E of different types are beneficial for chronic pain. To advance the research field, it might instead be interesting to add a focus on the physiological and neurobiological effect mechanisms associated to acute and long-term effects of PA&E in chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations